Investor Sentiment and South African Commodity Market Returns: Evidence from Switching Conditions - Moodley, Fabian; Ferreira-Schenk, Sune; Matlhaku, Kago (International Journal of Economics and Financial Issues, 2025)
The commodity market of emerging markets has over the years been a firm favourite among investors wanting to diversify their holding due to its safe heaven properties. Until recently, such properties have been criticised by academics due to its inability to provide portfolio protection during sentiment induced markets and market uncertainty. To this end, the objective of the study is to examine the effect of investor sentiment on South African commodity market returns during stable and volatile market conditions. In doing so, the study used monthly data for the period March 2007 to January 2024 to construct an investor sentiment index and test it against gold and oil returns. The findings of the Markov regime-switching model revealed that the return of gold is negatively significantly affected by investor sentiment in a bull regime, but oil returns is positively significantly affected by investor sentiment in the same regime. In a bear regime, investor sentiment has a positive significant effect on gold returns but in the same regime investor sentiment has a negative significant effect on oil returns. Moreover, the returns of gold and oil demonstrate bullish behaviour over the sample period. The findings demonstrate that during market uncertainty and sentiment induced markets, investors can incorporate gold in their portfolio to enhance diversification and limit losses, but the incorporation of oil will not yield any safe heaven properties. Similarly, the commodity market demonstrates adaptive behavioural as such financial market authorities must develop policies to reduce the alternating efficiencies caused by market conditions as it leads to miss-pricing and irrational investors.